2006
DOI: 10.1080/00365510500406910
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of red cell parameters on the Sysmex XE 2100 and ADVIA 120 in iron deficiency and in uraemic chronic disease

Abstract: This study confirmed the validity of RBC-Y in the management of ID, but not in RDT, where the diagnostic power of RBC-Y as an index of cell hypochromia is limited owing to high MCV values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 26 publications
2
21
0
2
Order By: Relevance
“…Ret-He is a measure of the forward scatter of stained reticulocytes and has a curvilinear relationship with CHr. RetHe values can be mathematically converted into reticulocyte hemoglobin concentration values that mirror the CHr values obtained on the Advia analyzers [8][9][10]. The average CHr value for healthy individuals using the Advia analyzer has been reported to be 30.8 pg with no difference between male and female subjects [3].…”
Section: Technical Aspects and Performancementioning
confidence: 99%
“…Ret-He is a measure of the forward scatter of stained reticulocytes and has a curvilinear relationship with CHr. RetHe values can be mathematically converted into reticulocyte hemoglobin concentration values that mirror the CHr values obtained on the Advia analyzers [8][9][10]. The average CHr value for healthy individuals using the Advia analyzer has been reported to be 30.8 pg with no difference between male and female subjects [3].…”
Section: Technical Aspects and Performancementioning
confidence: 99%
“…2 Therefore, human TfS, in direct correlation with serum iron concentration, decreases and remains reduced during ID or inflammation. 5 In cases of ID and concomitant disease such as inflammatory disorders, interpretation of biochemical iron panels is not diagnostically conclusive for ID in people due to complex confounding mechanisms, such as diurnal variation and variability of serum iron [10][11][12] , decreased serum iron due to hepcidin production in inflammatory diseases 13 , and transferrin being a negative acute phase reactant. In addition, TfS is unreliable 12 , and ferritin values can be increased due to the presence of inflammatory cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…5 In cases of ID and concomitant disease such as inflammatory disorders, interpretation of biochemical iron panels is not diagnostically conclusive for ID in people due to complex confounding mechanisms, such as diurnal variation and variability of serum iron [10][11][12] , decreased serum iron due to hepcidin production in inflammatory diseases 13 , and transferrin being a negative acute phase reactant. In addition, TfS is unreliable 12 , and ferritin values can be increased due to the presence of inflammatory cytokines. 13,14 Decreased erythropoiesis during ID, in combination with hemorrhage and a reduced lifespan of iron-deficient RBCs, can result in a complex form of iron deficiency anemia (IDA).…”
Section: Introductionmentioning
confidence: 99%
“…Ret He, generated by all Sysmex XE analysers (Sysmex Corporation, Kobe, Japan), has been recognised as a direct assessment of the incorporation of iron into erythrocyte hemoglobin and a direct estimate of the recent functional availability of iron into the erythron, thus provides the same information as CHr (Thomas et al, 2005;David et al, 2006). Twenty nine pg is the cut off value that defines deficient erythropoiesis Several studies have demonstrated that Ret He and CHr have the same clinical meaning (Mast et al, 2008;Maconi et al, 2009;Miwa et al, 2010).…”
Section: Wwwintechopencommentioning
confidence: 99%